Quality of life, pain and anxiety in patients with nephrostomy tubes - Luis Manuel Fernández-Cacho; Rosa Ayesa-Arriola
Objective: to evaluate the impact on the quality of life as well as anxiety and pain in patients with nephrostomy tubes. Method: this is a longitudinal descriptive study performed on a sample of n=150 patients. To evaluate the quality of life, the EuroQol-5D questionnaire was used; anxiety was quantified by the Beck Anxiety Inventory; to study pain, a visual analogue scale was employed. Results: statistically significant differences were found in the quality of life, with its worsening (r = 0.51; p <0.01) when evaluated at the first tube replacement. Patients presented mild to moderate anxiety before the procedure, which was reduced at the first tube replacement, although this difference was not significant (r = 0.028, p = 0.393). Finally, the degree of pain was also significantly reduced (r = 0.13, p<0.01) after six weeks. As for gender, women presented the worst values in the three variables studied (worse quality of life and greater anxiety and pain). Conclusions: nephrostomy tubes have a negative impact on the patient's quality of life. During the time they live with these tubes, patients have mild to moderate pain and anxiety.